A proposal for a data base system for export companies in Turkey - Tanyü, Ahmet. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 1984., 1984)
Nowadays, business activities in Turkey are performed mostly by means of manual Information Systems techniques and by the help of experienced teams and experts. The need for this kind of qualified personnel in organizations increases as a result of the increase in business activi·ties. Today, one of the most important problems for exporters, importers and banks is the complexity of export-import procedures and the associated information flow. Therefore, there must be a well-structured Management Information System in order to process accurate information for supporting decisions and controllirig the operations. In this study, Information Systems for only export companies have been studied. First, the export companies are analyzed and their problems are studied. Then, the data model are developed for the execution stage of an export activity. Also, the files and the computer programs are developed and implemented to the computer.
Keywords: Management information systems.